A Correlation Between Knowledge and Motivation of Pregnant Women With the Implementation of Maternal Classes in the Working Area of Megang Sakti Health Center - Rita Susanti; Taufianie Rossita; Mepi Sulastri (Universitas Dehasen Bengkulu, 2026)
Prenatal exercise is a beneficial form of physical activity because it develops body muscles, increases the elasticity of pelvic floor muscles and ligaments, reduces bleeding during and after delivery, and can reduce the incidence of fetal distress. Exercise is also a form of coping that can prevent physical stress caused by pregnancy, such as reducing leg and back cramps and improving the mother's ability to adapt to changes in her body. This study was a descriptive correlational study using a cross-sectional design. The independent variables were the knowledge and motivation of pregnant women, while the dependent variable was the implementation of prenatal classes. The sampling technique used was total sampling, with a sample size of 55 pregnant women. Data collection used a questionnaire. Data analysis used univariate and bivariate methods. The results of the univariate analysis showed that the majority of pregnant women in the Megang Sakti Health Center had good knowledge of prenatal exercise (44 women, 80.0%). 39 (70.9%) of pregnant women were highly motivated to attend prenatal classes, and 26 (47.3%) of pregnant women attended prenatal classes. The bivariate analysis yielded a p-value of 0.013, indicating a relationship between knowledge and prenatal class implementation. A significant result was also obtained with a p-value of 0.016, indicating a correlation between prenatal motivation and prenatal class implementation (p<0.05). Given the importance of prenatal exercise for maternal health, it is hoped that community health centers, as primary care providers, will be able to increase health promotion about prenatal exercise, facilitate prenatal exercise activities, and encourage community support for regular prenatal exercise activities.